Community Readiness In Supporting The Development of The Lequiraka Tourism Area In Municipality of Viqueque, Timor-Leste - Jesus Pereira Babo, Maria Ligia de; Sunarminto, Tutut; Sunkar, Arzyana (Devotion : Journal of Research and Community Service, 2022)
The wealth of nature, diversity of culture, and value of history possessed by Timor-Leste are essential potential triggers for developing the tourism sector. The provision of infrastructure in the tourism area, improvement of historical buildings, and promotion of the wealth of natural as well as cultural abroad have been carried out by the government to attract visitors to be able to visit Timor-Leste. The main target of the development of the tourism sector is increasing income and community’s welfare. One of the places used to promote destination tourism is Lequiraka. The purpose of this study is to assess the readiness of the people of Ossorua Village to support the development of the Lequiraka tourism area. The study was conducted in the village of Ossorua for two months, from September to October 2021. The data collection method was a preliminary survey and interviews with thirty people from the communities of Ossorua Village. The data analysis using the Likert analysis scale 1-5 to determine the readiness of the Ossorua village community to support the development of the tourism area and then described descriptively. Community have a moderate level of education (43%), involvement in the development activities of the development area is considered good. The community's readiness is considered good because it is seen from the level of education, community involvement, and participation is very supportive of the development of the tourism area.